Passive Q-switching operation of erbium-doped fiber laser with gold nanoparticles embedded into PVA film as saturable absorber - Muhammad, Ahmad Razif; Rosol, Ahmad Haziq Aiman; Tahrin, Rabiatul Addawiyah Azwa; Azman, Nursyafiqa; Kassim, Syara; Ismail, Mohd Afiq; Jusoh, Zulzilawati; Harun, Sulaiman Wadi (National Institute R & D of Materials Physics, 2019)
We demonstrate a Q-switched Erbium-doped fiber laser (EDFL) using a newly developed gold nanoparticles (GNPs) based saturable absorber (SA) for the first time. The GNPs were embedded in polyvinyl alcohol (PVA) for film-forming and inserted into an Erbium-doped fiber laser (EDFL) cavity to achieve passive Q-switching. The Q-switched EDFL operates at 1560 nm with a pump power threshold of 35 mW, a pulse repetition rate tunable from 19.7 to 89.9 kHz, and the smallest pulse-width of 2.64 µs. The Q-switching pulse shows no spectral modulation with a peak-to-pedestal ratio of 69 dB indicating the high stability of the laser. The highest pulse energy of 103 nJ was obtained at 118 mW pump power. These results show that the GNPs based SA is available for pulsed operation in the 1550 nm spectral range. © 2019, S.C. Virtual Company of Phisics S.R.L. All right reserved.